Secretory Phospholipase A2 Tipe II (SPLA II) Pada Penyakit Kardiovaskuler - Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2014)
Inflammatory reactions contribute to the pathogenesis of cardiovascular conditions such as atherosclerosis and ischemic damage in acute myocardial infarction (AMI). Among the mediators involved in inflammation are secretory phospholipase A2 group II (sPLA2-II) enzymes. Though some cells constitutively express Spla2-II, the synthesis by cells such as hepatocytes is typical for an acute-phase reactant. Recent literature suggest multiple roles for sPLA2-II in cardiovascular disease. In this review we discuss the role of sPLA2-II in included that sPLA2-II appears to be an inportant inflammatory mediator of cardiovascular disease.